Church reform and social change in eleventh-century Italy Dominic of Sora and his patrons - Howe, John 1947- (Univ. of Pennsylvania Press, 1997)
At the dawn of the second millennium, new churches and castles sprang up throughout Western Europe. In central Italy, St. Dominic of Sora (d. 1032) and his patrons played a key role in this process. John Howe mines the surprisingly rich but heretofore neglected sources that tell their story. He has written an absorbing case study of an ecclesiastical reform that was earlier - if less literate and less centralized - than the Gregorian Reform that would soon follow. At the center of his book is Dominic, a well-documented saint, hermit, abbot, and founder of monastic establishments, whose life and career reveal how central Italy was transformed during the first part of the eleventh century by the creation of walled hilltop villages and the establishment of unparalleled numbers of monasteries. In this lively and readable book, Howe argues that reform in the world of the eleventh century meant restoring lands, building churches, regularizing the clergy's distinctive garb, and changing the celebration of the liturgy. Much of what Dominic and his patrons accomplished soon became obsolete, swept aside by a more legalistic and coherent reform ideology. Yet nearly a thousand years later, traces of the new order that Dominic and his followers created can still be found in the Italian countryside.
Keywords: Dominique <de Sora, saint, 951-1031 ou 2>; Dominic <of Sora, Saint, 951-1031 or 2>; Dominicus -- von Sora -- 951-1031; Benediktiner; Kloster Montecassino; Geschichte 950-1100; Geschichte 1000-1100; Abbés - Italie - Biographies; Christendom; Hervormingen; Patronage ecclésiastique - Italie - Histoire; Saints chrétiens - Italie - Biographies; Sociale verandering; Église - Histoire - 11e siècle; Christentum; Geschichte; Kirchengeschichte; Sozialer Wandel; Abbots -- Italy -- Biography; Christian saints -- Italy -- Biography; Church history -- 11th century; Patronage, Ecclesiastical -- Italy -- History; Heiligenvita; Italie - Conditions sociales - 476-1268; Italien; Italy -- Social conditions; Biografie